Probabilistic Formulation of General Relativity and the Postulates of Relativity. - (:unkn) unknown (My University, 2012)
Recent developments at CERN have given more credibility to the postulated faster than the speed of light particles[1]. Regardless of the accuracy of the findings, the compounding evidence of the inaccuracies observed in Relativistic predictions of astronomical phenomena is enough to compel one to consider an alternative approach to explaining physical phenomena. We will also highlight some difficulties exposed by the postulates of Relativity, subsequent to which we will propose a probabilistic approach to GR.
Keywords: African Research